2020
DOI: 10.1590/s1678-9946202062093
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of epidemiological and quality indicators of health services for leprosy in hyperendemic areas in Northeastern Brazil

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
2
1
0
Order By: Relevance
“…In contrast, most of the new cases diagnosed during contact examination were men, which is consistent with the literature indicating higher leprosy transmission in men 27,28,29 , late diagnosis, and a higher probability of developing physical disabilities 25,30 .…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, most of the new cases diagnosed during contact examination were men, which is consistent with the literature indicating higher leprosy transmission in men 27,28,29 , late diagnosis, and a higher probability of developing physical disabilities 25,30 .…”
Section: Discussionsupporting
confidence: 90%
“…The analysis of the records used in this study found only 8 (0.3%) duplicate records, this being a proportion considered acceptable, corroborating the results found in the state of Mato Grosso (99.5%) regarding leprosy in children under 15 years of age, between 2001 and 2013, ( 22 as well as those of an evaluation of indicators for the state of Pernambuco between 2005 and 2014. 23 Despite the proportion of duplicates found (0.3%) being acceptable, the João Pessoa municipal surveillance service needs have a routine for finding duplicates, since repeated notifications lead to overestimation of case prevalence, thereby impacting the results of studies, calculation of indicators and planning of actions.…”
Section: Discussionsupporting
confidence: 87%
“…Temporal and spatial analyses have been developed to 1 understand the dynamics of leprosy in this country, identifying priority areas for health actions, aiming at early diagnosis and timely treatment. Despite the efforts, there are hyperendemic areas of leprosy in Brazil, demonstrating the persistence of this disease as a truly public health problem 3,4 .…”
Section: Introductionmentioning
confidence: 99%